Самостоятельность и управление производственным профилем предприятия - Градов А. П. Александр Петрович; Вещунов А. П. Анатолий Павлович; Вещунова Н. Л. Наталья Леонидовна; Волкова В. Н.; Козловская Э. А. (Москва, Экономика, 1990)
Исключено из фонда НТБ ТПУ